The family, society, and the individual - Jedlicka, Davor; Kephart, William (New York: Haper Collins, 1991)
Contents: Cultural and historical setting. American family varieties. Three premarital behavior patterns. Marital interaction and the family life course. The family and social change
Incluye bibliografía Includes bibliographical references and index
Keywords: Familia - Sociedad